Comparison of toxicity and outcomes of concurrent radiotherapy with carboplatin/paclitaxel or cisplatin/etoposide in stage III non–small cell lung cancer. (16th October 2013) - Liew, Mun Sem; Sia, Joseph; Starmans, Maud H. W.; Tafreshi, Ali; Harris, Sam; Feigen, Malcolm; White, Shane; Zimet, Allan; Lambin, Philippe; Boutros, Paul C.; Mitchell, Paul; John, Thomas
Abstract Concurrent chemoradiotherapy (CCRT) has become the standard of care for patients with unresectable stage III non–small cell lung cancer (NSCLC). The comparative merits of two widely used regimens: carboplatin/paclitaxel (PC) and cisplatin/etoposide (PE), each with concurrent radiotherapy, remain largely undefined. Records for consecutive patients with stage III NSCLC treated with PC or PE and ≥60 Gy chest radiotherapy between 2000 and 2011 were reviewed for outcomes and toxicity. Survival was estimated using the Kaplan–Meier method and Cox modeling with the Wald test. Comparison across groups was done using the student's t and chi‐squared tests. Seventy‐five (PC: 44, PE: 31) patients were analyzed. PC patients were older (median 71 vs. 63 years; P = 0.0006). Other characteristics were comparable between groups. With PE, there was significantly increased grade ≥3 neutropenia (39% vs. 14%, P = 0.024) and thrombocytopenia (10% vs. 0%, P = 0.039). Radiation pneumonitis was more common with PC (66% vs. 38%, P = 0.033). Five treatment‐related deaths occurred (PC: 3 vs. PE: 2, P = 1.000). With a median follow‐up of 51.6 months, there were no significant differences in relapse‐free survival (median PC 12.0 vs. PE 11.5 months, P = 0.700) or overall survival (median PC 20.7 vs. PE 13.7 months; P = 0.989). In multivariate analyses, no factors predicted for improved survival for either regimen. PC was more likely to be used in elderly patients. Despite this, PC resulted in significantly less hematological toxicity but achieved similar survival outcomes as PE. PC is an acceptable CCRT regimen, especially in older patients with multiple comorbidities.